The resistance evaluation: Effects of a specific training program on professional fire-fighter cardio-respiratory fitness - P.J. Mourão; F.J. Gonçalves (Desafio Singular, 2008)
The fire-fighters have an increased risk for developing cardiac pathologies and also a higher index of premature death than other individuals that perform high risk jobs. In this way, low physical fitness obviously limits fire-fighter performance, as well as degrades their health. However this fact not only damages the individual fire-fighter but also the institution that he represents hence severely questioning property and general public safety. The cardio-respiratory fitness had been identify as the most important physical fitness component. In this way, we developed a 12 weeks training program, to improve the cardio-respiratory fitness in a Professional fire-fighters corporation. According to reference values, before training these fire-fighters did not have enough cardio-respiratory fitness to adequately perform their job requirements with efficacy and safety (VO2máx=44,17ml/kg/min). However after training there was great improvement (VO2máx=52,69 ml/kg/min), providing a safe and more qualified service for the general population.